Tarcza Eliptyczna pod Wpływem Działania Obciążenia Zewnętrznego - Szelagowski, F. (Engineering Transactions, 1960)
The present paper contains a solution of the problem of an elliptical disc loaded on its edge. The problem reduces to the obtainment of two holomorphic functions φ(ζ) and F(ζ) appearing in the equations for the stresses Xy, Xy, Yy (Fig. 1) and the displacements u and v at any point of the region considered. Making use of the relations between the value of the holomorphic function inside the region and the value of its real and imaginary part on the edge, the final equations (24) and (26) are derived for the functions P(ζ) and F(ζ).